Vulvovaginal candidiasis (VVC) : A review of the literature - Dewi, Lidya Trisna (Bali Dermatology and Venereology Journal, 2020)
Vulvovaginal Candidiasis (VVC) is the second most common cause of vaginitis after bacterial vaginosis. VVC often occurs in women of reproductive age (20-40 years). Risk factors for VVC can be divided into two, such as host factors (pregnancy, hormone replacement, uncontrolled diabetes mellitus, immunosuppression, antibiotics, use of glucocorticoids, genetic influences) and behavioral factors (oralÃ‚Â  Ã‚Â contraceptives, cotraceptives and also some sexual habits, hygiene, and clothes that are used). To diagnose VVC in a person, evaluation from anamnesis and clinical manifestation can be conducted. It can also be confirmed by laboratory examination. The management based on the classification. Uncomplicated VVC is most effectively treated with topical azoles, but a single dose of fluconazole can also be given orally. Treatment of VVC with complications can be given fluconazole 150 mg for 3 days or topical azole for 7 days. However, when the VVC case that caused by Candida non-albicans not responding to conventional treatment such as antimycotics, the Ã‚Â Ã‚Â amphotericin B can be given to cure the disease. VVC caused by Candida glabrata can be given topical boric acid or flucytosine. This article consists of several theoretical references that has been viewed to have a better understanding regarding candidiasis vulvovaginitis.Ã‚Â